The prince of Egypt. (New York : DreamWorks, 1998)
Recounts the Biblical story of Moses.
From the motion picture of the same name.
Includes bibliographical references (p. 48).
At head of title on cover: Collector's edition storybook
Keywords: Moses -- (Biblical leader) -- Juvenile literature; Bible stories, English -- O.T. Exodus